A Canadian Guidance and Counselling Association Position Paper for the Provision of Counselling Services - Van Hesteren, Frank; Pawlovich, Walt (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper presents the Canadian Guidance and Counselling Associations' position statement regarding counselling services. More specifically, the paper places the evolution and current status of the position statement in historical perspective, articulates a rationale for the provision of counselling services, and describes the commitment of C.G.C. A. to meeting the needs of Canadian society.